Imagining One’s Own Infidel: Balkan Dhimmī Christians in Ottoman Historical Writing until 1600 - Rusev, Delyan (Studia Ceranea, 2024)
Non-Muslim dhimmīs, i.e. Christians and Jews, were an integral part of Ottoman society but left a negligible – and so far, largely neglected – trace in Ottoman (Muslim) historical writing of the fifteenth and the sixteenth centuries. While seeking to explain this phenomenon, the present paper analyzes the few identified historical accounts of Balkan Christians in the light of their authors’ personal backgrounds, ideological positions, and narrative strategies. It argues that there was no real historiographic discourse on the role of local Christians in the formation and functioning of the Ottoman state and society. Historians’ occasional interest in the topic was based on subjective factors such as greater access to relevant information or a penchant for thematic experimentation,with only a couple of accounts serving more pronounced didactic or ideological goals. The narratives primarily concern the utility and involvement of militarized Christian groups such as voynuqs and martoloses in Ottoman warfare, but some more abstract as well as visual representations are also discussed in the paper.